An adaptable CS-based transmission scheme in wireless sensor network. (5th June 2019) - Yang, Hao; Tang, Keming
As the essential requirement of wireless sensor network, energy-efficient data transmission has been paying a lot attention. Compressive sensing (CS) has been currently utilised to save consumption of sensors. However, a vital problem still remains unclear that whether the execution costs of sensors employing CS is not worth being considered, motivating us to explore the answer from a point of real deployment platform view. Presenting observations from our operating sensor network with 124 nodes, we verify two important facts: 1) The power costs of measure processing of sensors cannot be negligible as the increasing of samplings; 2) Measurements will constantly change along the routing and force relay sensors to consume more. Based on our findings, we propose an adaptable CS-based transmission scheme, ACS. With our experiments, energy is economised at least 15%. Our work gives a potential guideline for future designs of WSN in practice.